The impact of teacher attitude and teaching approaches on student demotivation: Disappointment as a mediator - Tang, Yeyao; Hu, Jifan (Frontiers in Psychology, 2022)
Student demotivation with English as a medium of instruction has attracted increased attention of scholars, particularly in those countries where it is taught as a second or foreign language. While there is a consensus that proficiency in English brings several benefits, it is found that students are demotivated to learn in English. As a result, many studies have tried to investigate the factors that reduce the motivation to learn in English. Drawing on disappointment theory, this study aims to investigate why and how the discouraging attitude of a teacher and discouraging teaching approaches create negative emotions (i.e., disappointment with English as a medium of instruction), which in turn demotivates Chinese students with English as a medium of instruction. This study has adopted a cross-sectional research design. The data were collected through a self-administered questionnaire survey from Chinese students (n = 428) studying in different universities in China. The hypothesized relationships were tested through PLS-based SEM by using Warp-PLS 7.0 software. The findings show that teachers' discouraging attitudes and discouraging teaching approaches are important determinants of student demotivation with English as a medium of instruction. The results also confirm that student disappointment is an important underlying mechanism in the relationship between exogenous and endogenous variables. This study contributes to the literature on student demotivation with English as a medium of instruction by superficially identifying teacher-related factors in China, which were previously overlooked. The implications of this study are that the university administration should monitor the attitude of the teachers toward English, as well as their teaching approaches, in order to curb any potential threat to student motivation. The administration should train the teachers on how to show a positive attitude and follow encouraging teaching approaches. In this way, students' disappointment with the English language and teaching methodology can also be overcome, which will ultimately increase their motivation with English as a medium of instruction in universities.